Graduate Enrollment in Bahrain’s Higher Education: A Descriptive Analysis of Gender and Program-Level Trends (The International Journal of Educational Sciences and Arts, 2025)
This study examines graduate enrollment trends in Bahrain’s higher education sector, situating them within global and Gulf Cooperation Council (GCC) contexts. Using official data from the Higher Education Council (HEC) via the Government of Bahrain’s Open Data Portal, the analysis covers academic years 2018/2019 to 2022/2023 across diploma, bachelor’s, master’s, and doctoral programs, disaggregated by gender and institutional sector. A descriptive quantitative design was applied, incorporating data aggregation, growth rate calculations, and gender ratio analysis. Descriptive statistics, trend analysis, and a Chi-Square Test of Independence were used to identify patterns and associations.The results indicate overall enrollment stability across the five-year period but with notable structural shifts. Diploma enrollments declined (CAGR = –1.8%), bachelor’s programs showed steady growth (CAGR = 6.0%), and postgraduate education expanded rapidly, with master’s (CAGR = 20.6%) and doctoral programs (CAGR = 28.5%) recording the strongest growth. Female students consistently outnumbered males at all levels, with disparities most pronounced at the master’s level (female-to-male ratio > 2:1). A Chi-Square Test confirmed a significant association between gender and program-level enrollment, χ² (3, N = 62,345) = 12.80, p = .005.These findings position Bahrain within broader international and regional trends, including the global shift toward advanced qualifications, employability-focused curricula, and digital transformation. Bahrain’s exceptionally high female participation distinguishes it from many OECD systems.
Keywords: Higher Education; Graduate Enrollment Trends; Bahrain